Endovascular clot retrieval for acute ischaemic stroke due to basilar artery occlusion in childhood. (3rd January 2020) - Macdonald‐Laurs, Emma; Wenderoth, Jason; Cardamone, Michael; Sampaio, Hugo; Andrews, P Ian
Abstract : Endovascular clot retrieval (ECR) is an emerging therapy for treatment of acute ischaemic stroke (AIS) in adults, including basilar artery occlusion (BAO). Its role in children is not well established. We report four consecutive children with AIS due to BAO treated with ECR in Sydney, Australia. We reviewed the literature to characterize the 'natural course' of AIS due to BAO in children not treated with thrombolysis or ECR, and compared their outcome with our patients and reported children with BAO treated with ECR. Despite delays in diagnosis, ECR achieved recanalization in our four children. Three children had a good outcome (Paediatric Modified Rankin Score [PedmRS] 0–2). One child with acute leukaemia suffered recurrent basilar occlusion and died of brainstem dysfunction. Literature review identified 111 children exhibiting the natural course of AIS due to BAO, among whom 42% had good outcomes (PedmRS 0–2), 48% had significant residual disability (PedmRS 3–5), and 10% died. Of 34 children treated with ECR, 28 (82%) had good outcomes (PedmRS 0–2), five (15%) had significant residual disability (PedmRS 3–5), and one (3%) died. Complications of ECR were uncommon. These observations suggest ECR may be beneficial for children with AIS due to BAO. What this paper adds: Children with acute ischaemic stroke (AIS) due to basilar artery occlusion (BAO) experience significant morbidity and mortality. Endovascular clot retrieval may be beneficial in children with AIS due to BAO. Abstract : This case series is commented on by Rennie on pages 1119–1120 of this issue.